A rust-proof lightweight high-strength plastic-steel composite material and preparation method thereof

By using a specially formulated anti-rust composite material in plastic steel materials and using the coordinated cooperation of multiple components, the problem of plastic steel materials being prone to rust after cleaning is solved, achieving efficient waterproofing and anti-rust effects of the material, while improving strength and compactness.

CN116478486BActive Publication Date: 2025-04-25SHENZHEN GAO KE PLASTICIZATION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310564279.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-18
Publication Date
2025-04-25
Estimated Expiration
2043-05-18

AI Technical Summary

Technical Problem

Plastic steel materials are prone to damage their protective film during cleaning, resulting in rust problems, and the prior art is difficult to effectively prevent this phenomenon.

Method used

It adopts a lightweight high-strength plastic steel composite material that is anti-rust, and its formula includes PVC resin, polyetherester elastomer fiber, antioxidant, rust-resistant agent, toughener, lubricant, filler, MAH grafted polyethylene, initiator, stabilizer, spiral carbon fiber and carbonyl iron powder. Through the special composite ratio and components, the waterproofness and rust resistance of the material are improved.

Benefits of technology

It significantly improves the waterproofness and rust resistance of plastic steel composite materials, reduces the rust situation of the material in humid environments, and improves the strength and density of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004236240330000051
    Figure BDA0004236240330000051
  • Figure BDA0004236240330000061
    Figure BDA0004236240330000061
Patent Text Reader

Abstract

The present application relates to the technical field of preparation of plastic-steel composite materials, and specifically discloses a rust-proof, lightweight, high-strength plastic-steel composite material and its preparation method. The rust-proof, lightweight, high-strength plastic-steel composite material of the present application is mainly made of the following raw materials: PVC resin, polyether ester elastic fiber, antioxidant, rust inhibitor, toughening agent, lubricant, filler, MAH grafted polyethylene, initiator, stabilizer, spiral carbon fiber, carbonyl iron powder; the preparation method comprises the following steps: uniformly mix PVC resin, polyether ester elastic fiber, antioxidant, rust inhibitor, toughening agent, lubricant, filler, MAH grafted polyethylene, initiator, stabilizer, spiral carbon fiber, carbonyl iron powder to obtain a mixture; extrude the mixture into water-cooled strips, and then pelletize to obtain. The rust-proof, lightweight, high-strength plastic-steel composite material prepared in the present application has good waterproofness and good rust resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of preparation of plastic-steel composite materials, and more specifically, to a rust-proof, lightweight, high-strength plastic-steel composite material and a preparation method thereof. Background Art

[0002] Plastic steel materials have excellent performance, easy processing and wide application. They are cheap, colorful, durable, have good thermal insulation and sound insulation properties. Due to their excellent physical properties such as rigidity, elasticity, corrosion resistance and aging resistance, plastic steel materials are also widely used in electronic engineering, automobiles, aerospace and other technical fields. At the same time, due to the excellent properties of plastic steel materials in terms of strength and hardness, and good elasticity and aging resistance, they can usually be used as a substitute for non-ferrous metals such as copper, zinc and aluminum.

[0003] The main component of plastic steel material is chemical polyvinyl chloride. Its raw material is polyvinyl chloride resin as the main raw material, and then a certain proportion of stabilizer, colorant, filler, UV absorber, etc. are added.

[0004] Plastic steel is mainly used as casement windows, guardrails, pipes and ceiling materials in house construction. It is not only light in weight, but also has good toughness and excellent properties of steel. It is sometimes called alloy plastic steel. When plastic steel is used as door and window materials, since the doors and windows processed by pure PVC profiles are not strong enough, steel is usually added to the cavity to enhance the firmness of the doors and windows.

[0005] When plastic steel materials are used as doors and windows, when the doors and windows are stained, they are generally cleaned with strong acid or strong alkali solutions.

[0006] Using strong acid or strong alkali solution for cleaning destroys the protective film of plastic steel, thereby destroying the protective film on the surface of the plastic steel material, causing the plastic steel material to rust. Summary of the invention

[0007] In order to improve the rust resistance of plastic-steel materials, the present application provides a rust-resistant, lightweight, high-strength plastic-steel composite material and a preparation method thereof.

[0008] In a first aspect, the present application provides a rust-proof, lightweight, high-strength plastic-steel composite material, which adopts the following technical solution:

[0009] A rust-proof, lightweight, high-strength plastic-steel composite material is mainly made of the following raw materials in parts by weight: 70-80 parts of PVC resin, 5-10 parts of polyether ester elastic fiber, 0.1-0.3 parts of antioxidant, 2-5 parts of rust inhibitor, 1-3 parts of toughening agent, 0.5-1 parts of lubricant, 2-5 parts of filler, 0.2-0.7 parts of MAH grafted polyethylene, 0.2-0.5 parts of initiator, 0.2-0.5 parts of stabilizer, 0.5-1 parts of spiral carbon fiber, 5-8 parts of carbonyl iron powder, wherein the rust inhibitor is at least two of n-oleyl sarcosine, benzotriazole, methyl vinyl silicone rubber, and N,N'-dimethyl-3,3'-dithiodipropionamide.

[0010] Preferably, the lubricant is any one of polyethylene wax and ethylene bisstearamide.

[0011] Preferably, the initiator is benzoyl peroxide.

[0012] Preferably, the stabilizer is zinc stearate.

[0013] Preferably, the antioxidant is a hindered phenol antioxidant; the hindered phenol antioxidant is antioxidant 1010.

[0014] By adopting the above technical scheme, the components in the rust-proof lightweight high-strength plastic-steel composite material of the present application adopt a special composite ratio, and the components cooperate with each other to improve the strength and density of the plastic-steel composite material, thereby improving the waterproofness and rust resistance of the plastic-steel composite material;

[0015] The carbonyl iron powder added to the plastic-steel composite material is a multifunctional metal powder material with an onion-shaped layered structure. At the same time, it has good wear resistance and structural properties. It is added to PVC resin to improve the wear resistance of the plastic-steel composite material.

[0016] Under the action of MAH grafted polyethylene, the rust inhibitor is evenly distributed in the plastic-steel composite material to improve the compatibility with other components in the plastic-steel composite material. The methyl vinyl silicone rubber in the rust inhibitor has better elasticity, absorbs water and swells, and cooperates with n-oleyl sarcosine to extend the water transmission path. N-oleyl sarcosine also reduces the aging of methyl vinyl silicone rubber; benzotriazole and N,N'-dimethyl-3,3'-dithiodipropionamide both form coordination bonds with metal atoms to form a multi-layer protective film in the plastic-steel composite material, thereby improving the rust resistance and water resistance of the plastic-steel composite material.

[0017] Preferably, the mass ratio of the polyether ester elastic fiber to the rust inhibitor is (7-8):(3-4).

[0018] By adopting the above technical scheme, the ratio of the two components of polyether ester elastic fiber and rust inhibitor is adjusted to achieve the best ratio of the two components. The polyether ester elastic fiber interacts with the rust inhibitor. The polyether ester elastic fiber not only has high strength but also has good elasticity. Part of the polyether ester elastic fiber is interwoven in the plastic-steel composite material to form an elastic network structure. The rust inhibitor is distributed in the elastic network structure. The polyether ester elastic fiber and the rust inhibitor cooperate with each other to jointly improve the waterproofness and rust resistance of the plastic-steel composite material.

[0019] Preferably, the rust inhibitor is composed of n-oleyl sarcosine, benzotriazole, methyl vinyl silicone rubber, and N,N'-dimethyl-3,3'-dithiodipropionamide in a mass ratio of (1-2):(4-5):(1-2):(1-2).

[0020] By adopting the above technical scheme, the rust inhibitor is obtained by compounding four components of n-oleyl sarcosine, benzotriazole, methyl vinyl silicone rubber, and N,N'-dimethyl-3,3'-dithiobispropionamide. The ratio of the four components is adjusted to make the ratio of the four components optimal. The methyl vinyl silicone rubber has better elasticity and expands after absorbing water, thereby further reducing the pore content in the plastic-steel composite material and helping to improve the waterproofness of the plastic-steel composite material; n-oleyl sarcosine is a polar organic additive with good adsorption capacity. At the same time, it has anti-wear, anti-rust and antioxidant effects, which is convenient for increasing the service life of methyl vinyl silicone rubber; benzotriazole may form covalent bonds and coordination bonds with metal atoms, and mutually replace each other to form polymers, so as to form a multi-layer protective film in the composite material to reduce the rust of the plastic-steel material under humid conditions; the thiol ions in N,N'-dimethyl-3,3'-dithiobispropionamide are adsorbed on the metal surface The active position on the surface of the steel sheet plays an anti-rust role, and the sulfur atom is essentially easy to form a coordination bond with the metal, and N,N'-dimethyl-3,3'-dithiobispropionamide contains nitrogen or oxygen ions at the same time, and the nitrogen or oxygen atoms may form a coordination bond with the surface of the iron powder. At the same time, N,N'-dimethyl-3,3'-dithiobispropionamide containing nitrogen and oxygen atoms is easy to form a chelate bond with the metal surface, which is convenient for adsorption on the metal surface, and N,N'-dimethyl-3,3'-dithiobispropionamide can be used as a cross-linking promoter for the resin film, and they cooperate with each other to reduce the number of micropores in the resin film and improve the waterproofness of the plastic-steel composite material; benzotriazole and N,N'-dimethyl-3,3'-dithiobispropionamide cooperate with each other and are adsorbed on the metal surface. On the premise of improving the rust resistance of the plastic-steel composite material, n-oleyl sarcosine reduces the aging of methyl vinyl silicone rubber. The four components cooperate with each other to improve the waterproofness and rust resistance of the plastic-steel composite material.

[0021] Preferably, the methyl vinyl silicone rubber is modified methyl vinyl silicone rubber, and the preparation method of the modified methyl vinyl silicone rubber comprises the following steps: immersing the methyl vinyl silicone rubber in methyl hydrogenated silicone oil and styrene acrylic emulsion in sequence to obtain pretreated methyl vinyl silicone rubber, mixing the pretreated methyl vinyl silicone rubber with water-swellable rubber, and drying to obtain the pretreated methyl vinyl silicone rubber.

[0022] Preferably, the particle size ratio of the water-swellable rubber to the methyl vinyl silicone rubber is 1:(3-5).

[0023] By adopting the above technical scheme, the methyl vinyl silicone rubber is immersed in methyl hydrogenated silicone oil, so as to improve the waterproofness of the methyl vinyl silicone rubber. The methyl vinyl silicone rubber is then immersed in styrene acrylic emulsion, so as to improve the adhesion of the methyl vinyl silicone rubber. The water-swelling rubber adheres to the surface of the methyl vinyl silicone rubber to form an elastic water-absorbing layer. The water-swelling rubber absorbs water and swells, thereby blocking the transmission of moisture. At the same time, the methyl vinyl silicone rubber is elastic, and the water-swelling rubber and the methyl vinyl silicone rubber are squeezed against each other, thereby further reducing the channel for moisture transmission, improving the density of the plastic-steel composite material, and then improving the waterproofness and rust resistance of the plastic-steel composite material.

[0024] Preferably, the method for preparing the methyl vinyl silicone rubber comprises the following steps: rolling the methyl vinyl silicone rubber mixture, adding polytetrafluoroethylene powder, mixing evenly, adding a vulcanizing agent, thinning, and forming sheets.

[0025] By adopting the above technical scheme, polytetrafluoroethylene has better corrosion resistance and chemical stability. When preparing methyl vinyl silicone rubber, polytetrafluoroethylene powder is added to improve the oil resistance of methyl vinyl silicone rubber. At the same time, the strength of methyl vinyl silicone rubber is improved, so as to further improve the strength of the plastic-steel composite material.

[0026] Preferably, the polytetrafluoroethylene is modified polytetrafluoroethylene, and the preparation method of the modified polytetrafluoroethylene comprises the following steps: immersing polytetrafluoroethylene powder in styrene-acrylic emulsion to obtain pretreated polytetrafluoroethylene, mixing the pretreated polytetrafluoroethylene with hydrophobic nano-silica, and drying to obtain modified polytetrafluoroethylene.

[0027] By adopting the above technical scheme, hydrophobic nano-silica is bonded to the surface of polytetrafluoroethylene to form a hydrophobic layer, so as to further improve the hydrophobicity of polytetrafluoroethylene, thereby improving the compatibility between polytetrafluoroethylene and methyl vinyl silicone rubber, thereby improving the strength and hydrophobicity of methyl vinyl silicone rubber, further enhancing the hydrophobicity of the plastic-steel composite material, and reducing the rust of the plastic-steel composite material.

[0028] Preferably, the filler is composed of polyurethane elastomer, chopped basalt fibers, and nano-ultrafine calcium carbonate in a mass ratio of (3-5):(1-2):(1-2).

[0029] By adopting the above technical scheme, the filler is compounded from three components: polyurethane elastomer, chopped basalt fibers, and nano-ultrafine calcium carbonate. The ratio of the three components is adjusted to achieve the best ratio. The nano-calcium carbonate has a steric hindrance effect and an anti-sedimentation effect. The chopped basalt fibers overlap each other to form a network structure. Part of the polyurethane elastomer may be filled in the pores of the network structure to form an elastic layer. The polyurethane elastomer and the chopped basalt fibers have good hydrophobicity, so a waterproof layer may be formed in the plastic-steel composite material to further improve the waterproofness of the plastic-steel composite material and improve the rust resistance of the plastic-steel composite material. The nano-calcium carbonate has a small particle size and may be filled between adjacent polyurethane elastomers and between the polyurethane elastomer and the chopped basalt fibers to reduce the porosity of the plastic-steel composite material and improve the density of the plastic-steel composite material. The chopped basalt fibers have high strength, which is convenient for improving the strength of the plastic-steel composite material.

[0030] Preferably, the toughening agent is composed of butadiene rubber and chlorinated polyethylene in a mass ratio of (1-2):(5-8).

[0031] By adopting the above technical solution, the toughening agent can improve the strength of PVC products, increase toughness, and promote plasticization during processing.

[0032] In a second aspect, the present application provides a method for preparing a rust-proof, lightweight, high-strength plastic-steel composite material, using the following technical solution:

[0033] A method for preparing a rust-proof, lightweight, high-strength plastic-steel composite material comprises the following steps:

[0034] (1) Preparation of a mixture: PVC resin, polyether ester elastic fiber, antioxidant, rust inhibitor, toughening agent, lubricant, filler, MAH grafted polyethylene, initiator, stabilizer, spiral carbon fiber, and carbonyl iron powder are uniformly mixed to obtain a mixture;

[0035] (2) Preparation of plastic steel material: The mixed material obtained in step (1) is extruded into water-cooled strips, and then pelletized to obtain the obtained material.

[0036] Preferably, the mixing in step (1) is performed using a mixer.

[0037] Preferably, in step (2), a twin-screw extruder is used for extrusion; and the extrusion temperature is 160-180°C.

[0038] By adopting the above technical scheme, the raw materials used in the preparation process of the plastic-steel material of the present application are easy to obtain, the process is simple, and it is easy to operate. The prepared plastic-steel material has high water resistance and strength.

[0039] In summary, this application has the following beneficial effects:

[0040] 1. Rust inhibitor and carbonyl iron powder are added to the rust-proof lightweight high-strength plastic-steel composite material of the present application. The rust inhibitor and carbonyl iron powder cooperate with each other and are evenly distributed in the plastic-steel composite material under the action of MAH grafted polyethylene, which is convenient for improving the density of the plastic-steel composite material, thereby improving the waterproofness and rust resistance of the plastic-steel composite material.

[0041] 2. The rust inhibitor in the rust-proof lightweight high-strength plastic-steel composite material of the present application is coordinated by four components: n-oleyl sarcosine, benzotriazole, methyl vinyl silicone rubber, and N,N'-dimethyl-3,3'-dithiobispropionamide, so as to further improve the waterproofness and rust resistance of the plastic-steel composite material. DETAILED DESCRIPTION

[0042] The present application is further described in detail below with reference to the embodiments.

[0043] Example

[0044] Embodiment 1: A rust-proof, lightweight, high-strength plastic-steel composite material, comprising the following raw materials by weight: 70 kg of PVC resin, 5 kg of polyether ester elastic fiber, 0.1 kg of antioxidant, 2 kg of rust inhibitor, 1 kg of toughening agent, 0.5 kg of lubricant, 2 kg of filler, 0.2 kg of MAH grafted polyethylene, 0.2 kg of initiator, 0.2 kg of stabilizer, 0.5 kg of spiral carbon fiber, and 5 kg of carbonyl iron powder, wherein the antioxidant is a hindered phenol antioxidant; the hindered phenol antioxidant is antioxidant 1010; the rust inhibitor is composed of n-oleyl sarcosine and benzotriazole in a mass ratio of 1:1, the lubricant is polyethylene wax, the toughening agent is composed of butadiene rubber and chlorinated polyethylene in a mass ratio of 2:8, the filler is composed of polyurethane elastomer, chopped basalt fiber, and nano-ultrafine calcium carbonate in a mass ratio of 5:2:2; the initiator is benzoyl peroxide; and the stabilizer is zinc stearate.

[0045] The method for preparing the above-mentioned rust-proof lightweight high-strength plastic-steel composite material comprises the following steps: (1) preparing a mixture: uniformly mixing PVC resin, polyether ester elastic fiber, antioxidant, rust inhibitor, toughening agent, lubricant, filler, MAH grafted polyethylene, initiator, stabilizer, spiral carbon fiber, and carbonyl iron powder in a mixer to obtain a mixture;

[0046] (2) Preparation of plastic-steel material: The mixture obtained in step (1) is extruded into water-cooled strands in a twin-screw extruder, and then pelletized to obtain the obtained material, wherein the extrusion temperature is 175°C.

[0047] Table 1 Anti-rusting lightweight high-strength plastic-steel composite materials of Examples 1-4

[0048]

[0049]

[0050] Example 2-4: A rust-proof, lightweight, high-strength plastic-steel composite material, the raw material composition ratio is shown in Table 1, and the difference from Example 1 is that the raw material composition ratio is different.

[0051] Example 5: A rust-proof lightweight high-strength plastic-steel composite material, which is different from Example 4 in that the rust inhibitor is composed of n-oleyl sarcosine, benzotriazole, methyl vinyl silicone rubber, and N,N'-dimethyl-3,3'-dithiodipropionamide in a mass ratio of 1:4:1:1. The methyl vinyl silicone rubber is commercially available.

[0052] Example 6: A rust-proof lightweight high-strength plastic-steel composite material, which is different from Example 4 in that the rust inhibitor is composed of n-oleyl sarcosine, benzotriazole, methyl vinyl silicone rubber, and N,N'-dimethyl-3,3'-dithiodipropionamide in a mass ratio of 2:5:2:2. The methyl vinyl silicone rubber is commercially available.

[0053] Example 7: A rust-proof, lightweight, high-strength plastic-steel composite material, which is different from Example 6 in that the methyl vinyl silicone rubber is a modified methyl vinyl silicone rubber, and the preparation method of the modified methyl vinyl silicone rubber comprises the following steps: immersing the methyl vinyl silicone rubber in methyl hydrogenated silicone oil and styrene acrylic emulsion in turn, the immersion time is 10 minutes, to obtain pretreated methyl vinyl silicone rubber, mixing the pretreated methyl vinyl silicone rubber with water-swelling rubber, and drying. Among them, the mass ratio of methyl vinyl silicone rubber to water-swelling rubber is 1:4, and the particle size ratio of methyl vinyl silicone rubber to water-swelling rubber is 4:1.

[0054] Embodiment 8: A rust-proof, lightweight, high-strength plastic-steel composite material, which is different from Embodiment 6 in that: a method for preparing methyl vinyl silicone rubber comprises the following steps: rolling the methyl vinyl silicone rubber compound and adding polytetrafluoroethylene powder, mixing evenly, adding a vulcanizing agent, thinning, and producing a sheet. The vulcanizing agent is diisopropylbenzene peroxide. The mass ratio of the methyl vinyl silicone rubber compound to the polytetrafluoroethylene powder is 5:10.

[0055] Example 9: A rust-proof, lightweight, high-strength plastic-steel composite material, which differs from Example 8 in that the polytetrafluoroethylene is modified polytetrafluoroethylene, and the preparation method of the modified polytetrafluoroethylene comprises the following steps: impregnating polytetrafluoroethylene powder in styrene-acrylic emulsion for 10 minutes to obtain pretreated polytetrafluoroethylene, mixing the pretreated polytetrafluoroethylene with hydrophobic nano-silica in a mass ratio of 3:6, and drying to obtain modified polytetrafluoroethylene.

[0056] Comparative Example

[0057] Comparative Example 1: A rust-proof, lightweight, high-strength plastic-steel composite material, which differs from Example 1 in that no polyether ester elastic fiber is added.

[0058] Comparative Example 2: A rust-proof, lightweight, high-strength plastic-steel composite material, which differs from Example 1 in that no rust inhibitor is added.

[0059] Comparative Example 3: A rust-proof, lightweight, high-strength plastic-steel composite material, which differs from Example 1 in that the rust inhibitor is n-oleyl sarcosine.

[0060] Detection Methods

[0061] Tensile strength test: The rust-proof lightweight high-strength plastic-steel composite materials prepared in Examples 1-9 and Comparative Examples 1-3 were taken, and the tensile strength of the rust-proof lightweight high-strength plastic-steel composite materials was tested according to the test method in GB / T1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics". The test results are shown in Table 2.

[0062] Water vapor permeability test: Take the rust-proof lightweight high-strength plastic-steel composite materials prepared in Examples 1-9 and Comparative Examples 1-3, and test the water vapor permeability of the rust-proof lightweight high-strength plastic-steel composite materials according to the test method in YBB00212005 "Polyvinyl chloride solid pharmaceutical hard tablets". The test results are shown in Table 2.

[0063] Table 2 Performance test of rust-proof lightweight high-strength plastic-steel composite materials of Examples 1-9 and Comparative Examples 1-3

[0064] Serial number <![CDATA[Water vapor transmission rate (m 2 , 24 h)]]> Tensile strength MPa Example 1 2.1 42.5 Example 2 1.9 43.6 Example 3 2.0 42.8 Example 4 1.8 43.9 Example 5 1.6 44.5 Example 6 1.5 44.9 Example 7 1.2 45.7 Example 8 1.3 45.5 Example 9 1.1 46.3 Comparative Example 1 2.8 38.1 Comparative Example 2 3.3 38.5 Comparative Example 3 3.0 38.8

[0065] In combination with Example 1 and Comparative Examples 1-3, and in combination with the data in Table 2, it can be seen that the rust-proof, lightweight, high-strength plastic-steel composite material obtained in Example 1 has better water resistance and tensile strength. The polyether ester elastic fiber and the rust inhibitor in Example 1 interact with each other and cooperate with each other to improve the tensile strength and water resistance of the plastic-steel composite material and reduce the rust of the plastic-steel composite material.

[0066] In combination with Examples 1-4 and the data in Table 2, it can be seen that the plastic-steel composite materials obtained in Examples 1-4 have lower water vapor permeability and higher tensile strength. The ratio of the raw material components of the rust-proof lightweight and high-strength plastic-steel composite materials is adjusted to improve the performance of the plastic-steel composite materials.

[0067] In combination with Examples 4-6 and the data in Table 2, it can be seen that the waterproofness of the rust-proof lightweight high-strength plastic-steel composite material obtained in Examples 5-6 is better than the waterproofness of the rust-proof lightweight high-strength plastic-steel composite material obtained in Example 4, and the tensile strength is higher. The inventors of the present application believe that: when the rust inhibitor is compounded from four components of n-oleyl sarcosine, benzotriazole, methyl vinyl silicone rubber, and N,N'-dimethyl-3,3'-dithiobispropionamide, on the one hand, the water resistance of the rust-proof lightweight high-strength plastic-steel composite material is improved, and on the other hand, the tensile strength of the rust-proof lightweight high-strength plastic-steel composite material is improved.

[0068] In combination with Example 6 and Example 7, and in combination with the data in Table 2, it can be seen that the water resistance and tensile strength of the rust-proof lightweight high-strength plastic-steel composite material obtained in Example 7 are better. The difference between Example 7 and Example 6 is that Example 7 modifies the methyl vinyl silicone rubber in the rust inhibitor. The inventor of the present application believes that after the methyl vinyl silicone rubber is modified, it is added to the rust-proof lightweight high-strength plastic-steel composite material, and the obtained rust-proof lightweight high-strength plastic-steel composite material has better performance.

[0069] In combination with Example 6, Examples 8-9, and the data in Table 2, it can be seen that the rust-proof, lightweight, high-strength plastic-steel composite materials obtained in Examples 8-9 have better water resistance and tensile strength. The difference between Example 8 and Example 6 is that Example 8 uses homemade methyl vinyl silicone rubber, and Example 9 modifies polytetrafluoroethylene. The inventors of the present application believe that homemade methyl vinyl silicone rubber and modified polytetrafluoroethylene used for homemade methyl vinyl silicone rubber can produce a rust-proof, lightweight, high-strength plastic-steel composite material with better performance.

[0070] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A rust-proof, lightweight, high-strength plastic-steel composite material, characterized in that: It is mainly made of the following raw materials in parts by weight: 70-80 parts of PVC resin, 5-10 parts of polyether ester elastic fiber, 0.1-0.3 parts of antioxidant, 2-5 parts of rust inhibitor, 1-3 parts of toughening agent, 0.5-1 parts of lubricant, 2-5 parts of filler, 0.2-0.7 parts of MAH grafted polyethylene, 0.2-0.5 parts of initiator, 0.2-0.5 parts of stabilizer, 0.5-1 parts of spiral carbon fiber, and 5-8 parts of carbonyl iron powder; The mass ratio of the polyether ester elastic fiber to the rust inhibitor is (7-8):(3-4); The rust inhibitor is n-oleyl sarcosine and benzotriazole in a mass ratio of 1:1 or n-oleyl sarcosine, benzotriazole, methyl vinyl silicone rubber and N,N'-dimethyl-3,3'-dithiodipropionamide in a mass ratio of 1:4:1:

1.

2. The rust-proof, lightweight, high-strength plastic-steel composite material according to claim 1, characterized in that: The methyl vinyl silicone rubber is modified methyl vinyl silicone rubber. The preparation method of the modified methyl vinyl silicone rubber comprises the following steps: immersing the methyl vinyl silicone rubber in methyl hydrogenated silicone oil and styrene acrylic emulsion in sequence to obtain pretreated methyl vinyl silicone rubber, mixing the pretreated methyl vinyl silicone rubber with water-swellable rubber, and drying to obtain the pretreated methyl vinyl silicone rubber.

3. The rust-proof, lightweight, high-strength plastic-steel composite material according to claim 1, characterized in that: The preparation method of methyl vinyl silicone rubber comprises the following steps: rolling the methyl vinyl silicone rubber mixed rubber, adding polytetrafluoroethylene powder, mixing evenly, adding a vulcanizing agent, thinning, and forming a sheet to obtain the obtained product.

4. The rust-proof, lightweight, high-strength plastic-steel composite material according to claim 3, characterized in that: The polytetrafluoroethylene is modified polytetrafluoroethylene. The preparation method of the modified polytetrafluoroethylene comprises the following steps: immersing polytetrafluoroethylene powder in styrene-acrylic emulsion to obtain pretreated polytetrafluoroethylene, mixing the pretreated polytetrafluoroethylene with hydrophobic nano-silicon dioxide, and drying to obtain modified polytetrafluoroethylene.

5. The rust-proof, lightweight, high-strength plastic-steel composite material according to claim 1, characterized in that: The filler is composed of polyurethane elastomer, short-cut basalt fibers and nano-ultrafine calcium carbonate in a mass ratio of (3-5):(1-2):(1-2).

6. The rust-proof, lightweight, high-strength plastic-steel composite material according to claim 1, characterized in that: The toughening agent is composed of butadiene rubber and chlorinated polyethylene in a mass ratio of (1-2):(5-8).

7. A method for preparing the rust-proof, lightweight, high-strength plastic-steel composite material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: (1) preparing a mixture: uniformly mixing PVC resin, polyether ester elastic fiber, antioxidant, rust inhibitor, toughening agent, lubricant, filler, MAH grafted polyethylene, initiator, stabilizer, spiral carbon fiber and carbonyl iron powder to obtain a mixture; and (2) preparing a plastic steel material: extruding the mixture obtained in step (1) into water-cooled strips, and then pelletizing to obtain the obtained material.

Citation Information

Patent Citations

  • Rust-proof anti-fog PE shrink film and processing method thereof

    CN111469520A

  • Motor oil for electric automobile and preparation method thereof

    CN112694938A